Time scale of glycation in collagen of bovine pericardium-derived bio-tissues. (2021) - Caro, Liberato De; Terzi, Alberta; Fusaro, Luca; Altamura, Davide; Boccafoschi, Francesca; Bunk, Oliver; Giannini, Cinzia
No abstract available